United Kingdom : Financial Sector Assessment Program-Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT)-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper sets out the findings and recommendations made in the context of the 2016 Financial Sector Assessment Program for the United Kingdom in the areas of Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT). Since the 2011 FSAP, steps have been taken to strengthen the AML/CFT regime. Although significant progress has been made since the United Kingdom's 2007 mutual evaluation against the previous Financial Action Task Force standard, the authorities are now in the process of bringing their AML/CFT framework in line with the prevailing standard, which was revised in 2012. The United Kingdom has recently adopted a comprehensive reform package to enhance entity transparency.